2012
DOI: 10.1007/s10832-012-9708-5
|View full text |Cite
|
Sign up to set email alerts
|

Large signal response and harmonic distortion in piezoelectrics for SONAR transducers

Abstract: Nonlinearity in the piezoelectric response limits the operating conditions of underwater transducers. In this work, the nonlinear effects are evaluated in terms of electrical current and induced strain as a function of drive level. Nonlinearity is further quantified within the active transduction material by evaluating the total harmonic distortion (THD) in the electromechanical response. Modified single crystals based on the binary lead magnesium niobate-lead titanate system were investigated. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Electromechanically functional materials are of primary interest in various applications such as electromechanical sensors, 1 sonar, 2 artificial muscles, 3 and ultrasonic transducers. 4 In piezoelectrics, the electromechanical response can be classified into direct and inverse piezoelectric effects.…”
Section: Introductionmentioning
confidence: 99%
“…Electromechanically functional materials are of primary interest in various applications such as electromechanical sensors, 1 sonar, 2 artificial muscles, 3 and ultrasonic transducers. 4 In piezoelectrics, the electromechanical response can be classified into direct and inverse piezoelectric effects.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, research into the nonlinear properties of ferroelectric capacitor structures has been studied theoretically by Boser1718, (developing earlier statistical physics analyses by Kronmüller19) and extended with experimental investigations by Damjanovic202122 and Trolier-McKinstry et al 2324. Other significant experimental252627 and theoretical28 studies on harmonic analysis have also been reported. However, these measurements have generally been performed on macroscopic systems, e.g.…”
mentioning
confidence: 96%